Un texto bizantino medieval. El Milagro XXIII - García Álvarez, César (Byzantion Nea Hellás, 2015)
It is a well known fact that twelfth century Spain’s greatest poet was Gonzalo de Berceo. In his work The Miracles of Our Lady, a Marian legend of Byzantine theme is poetized, the XXIII Miracle "La deuda pagada". The Spanish poet, with almost absolute certainty, used as his source the Ms. Thott 128 of Copenhague. Having as its aim to delve into Berceo’s literary originality, Professor García draws a comparison between both texts. Although professor García had already undertaken a similar research in number 5 (1981) of Byzantion Nea Hellas, now he pursues the same aim includng in his comparison two manuscripts recently discovered, one belonging to the Biblioteca Nacional of Madrid, the other to the Biblioteca Nacional of Lisboa.